Risk Factors of Bone Nonfusion After Spinal Tuberculosis Debridement Bone Graft Fusion and Internal Fixation - Wei, Zihan; Zhang, Ying; Yang, Sizhen; Ye, Jiawen; Hu, Xu; Li, Tian; Chu, Tongwei (Frontiers in Surgery, 2022)
Objective: To retrospectively analyze bone graft nonfusion risk factors in spinal tuberculosis patients after lesion debridement, bone graft fusion and internal fixation. Methods: The clinical data of 131 patients who underwent spinal tuberculosis debridement, bone graft fusion and internal fixation in our hospital from March 2015 to March 2018 were retrospectively analyzed. The patients were divided into two groups according to bone fusion after the operation; there were 37 patients in the nonfusion group and 94 in the fusion group. The basic information and follow-up data of the patients were collected to evaluate the risk factors for bone graft nonfusion 1 year after surgery. Results: The severity of osteoporosis in the nonfusion group was significantly greater than that in the fusion group (p < 0.05). There were statistically significant differences between the two groups in terms of continuous multisegment status, disease duration, intraoperative surgical methods and whether patients received standardized drug treatment for 12 months after surgery (p<0.05). Multivariate logistic regression analysis showed that long disease duration, posterior approach, and degree of osteoporosis were risk factors for postoperative bone graft nonfusion (OR>1, p<0.05), while standard drug treatment for 1 year after surgery was a protective factor (OR<1, p<0.05). Conclusion: Spinal tuberculosis patients who had a long disease course, who underwent simple posterior debridement, or who had severe osteoporosis had a higher risk of bone graft nonfusion after surgery. Tuberculosis treatment is beneficial for the osseous fusion of the postoperative bone graft area.